An Empirical Study on Human Resource Management and Employment Performance Practice in the Banking Sector in Bangladesh - Miah, Mohammad Sharif; Hossain, Nazmul; Nishat, Abu Jakaria (Advances in Social Sciences Research Journal, 2021)
Banking sector is one of the first growing sectors in Bangladesh. Like any other emerging economic sector banking sector’s growth and development needed to be assess and evaluated through employment performance. There are 56 commercial banks in Bangladesh currently offering financial service with different stratagems. Performance evaluation and assessment is significantly important while achieving the goals of the organization and determining the individual contributions to the organization. The objective of the study is to measure the effects of human resource practice on the performance of employee in the banking sector of Bangladesh. The research has been conducted through structural and semi-structural questionnaires and face-to-face interview related to some human resource issues namely-institutional commitment and motivation, employee relations, compensation, physical work environment, training and development, promotion, job satisfaction as well as the employee performance of the designed banks. A set of 30 structural and same number of semi structural questionnaires were given to 328 bank employees of different levels of 10 selected banks. According to the study all the human resource practice including compensation and training & development have significant impact on the employee performance in the banking sector in Bangladesh. The findings of the study provide a clear guidance to the banking policy makers to pursue effective initiatives with in order to achieve organizational goal through the employee performance.